The International Childhood Cancer Cohort Consortium (I4C): A research platform of prospective cohorts for studying the aetiology of childhood cancers - Tikellis, G; Dwyer, T; Paltiel, O; Phillips, GS; Lemeshow, S; Golding, J; Northstone, K; Boyd, A; Olsen, S; Ghantous, A; Herceg, Z; Ward, MH; et al. (Wiley, 2018)
Background Childhood cancer is a rare but leading cause of morbidity and mortality. Established risk factors, accounting for <10% of incidence, have been identified primarily from case‐control studies. However, recall, selection and other potential biases impact interpretations particularly, for modest associations. A consortium of pregnancy and birth cohorts (I4C) was established to utilise prospective, pre‐diagnostic exposure assessments and biological samples. Methods Eligibility criteria, follow‐up methods and identification of paediatric cancer cases are described for cohorts currently participating or planning future participation. Also described are exposure assessments, harmonisation methods, biological samples potentially available for I4C research, the role of the I4C data and biospecimen coordinating centres and statistical approaches used in the pooled analyses. Results Currently, six cohorts recruited over six decades (1950s‐2000s) contribute data on 388 120 mother‐child pairs. Nine new cohorts from seven countries are anticipated to contribute data on 627 500 additional projected mother‐child pairs within 5 years. Harmonised data currently includes over 20 “core” variables, with notable variability in mother/child characteristics within and across cohorts, reflecting in part, secular changes in pregnancy and birth characteristics over the decades. Conclusions The I4C is the first cohort consortium to have published findings on paediatric cancer using harmonised variables across six pregnancy/birth cohorts. Projected increases in sample size, expanding sources of exposure data (eg, linkages to environmental and administrative databases), incorporation of biological measures to clarify exposures and underlying molecular mechanisms and forthcoming joint efforts to complement case‐control studies offer the potential for breakthroughs in paediatric cancer aetiologic research.